Bibliometric and Visualized Analysis of Scientific Publications on Geotechnics Fields - Isah Bela Mulyawati; Doni Fajar Ramadhan (Universitas Pendidikan Indonesia (UPI), 2021)
The advancement of civil engineering plays a major role in determining the nation's development. Generally, geotechnical engineering has a great influence as there is a building on the ground. The facts show that there are still many geotechnical problems that arise during the development process. One of the supporting factors in dealing with these problems is the development of research in the geotechnical sector in various fields. This research aims to determine the development of research related to Geotechnical Engineering through a bibliometric distribution map using the VOSviewer application. Data collection is gathered from the dimension site. The keyword used in this study is